The Role of Training and Career Development in Efforts to Improve Employee Performance in Regional Public Companies - Rama Faiz Rustandi; Fikri Bayu Nur Rizal (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine and understand the role of training and career development in efforts to improve employee performance in regional public companies. This research uses quantitative methodologies with a sample size of 240 people. This research used a sample size of 151 participants, which was determined using the Slovin method with a 5% margin of error. In order to gather data, interviews, surveys, and questionnaires were used. Both characteristics were shown to significantly affect employee performance in the research. Training and career development are critical components in enhancing overall employee performance, as this finding proves. This further supports the idea that public sector organizations in the area may benefit greatly from training and career development programs in order to achieve their full potential.